Audit and ethic simulation games (AEStiG) / Razana Juhaida Johari … [et al.] - Johari, Razana Juhaida; Mohd Sanusi, Zuraidah; Paino, Halil; Mat Isa, Yusarina; Shafie, Nur Aima (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
AEStiG is a multimedia interactive financial auditing and ethic cases simulation. This e-learning tool is meant for a classroom and training module for the auditors to be as well as the new audit staff of the audit firms. AEStiG comprises of two segments which captures the technical and soft skills that were expected from the auditors. This product provides comprehensive and interactive audit simulation which provides users with real audit environment. It challenges the users to decide on the appropriate audit planning, audit evidence selection and usage of appropriate audit procedures. Besides, this product could also be used to observe the ethical consideration of auditors in making decisions, which is important to enhance the public confidence. Success in properly acquiring audit evidence and dealing with the client as well as having a sound ethical consideration will affect the outcome of the simulated audit. The first of its kind, this game is suitable to be used within Malaysian higher education environment and audit firms. It can be commercialized through collaboration with Bahagian Teknologi Pendidikan Mistery of Higer Education as well with Malaysia Institute of Accountants